TAREKAT AS A MULTICULTURAL SPACE: A LITERATURE STUDY ON THE INTEGRATION OF DIVERSITY VALUES IN SUFISM - Kholid Mawardi; Zein Muchamad Masykur; Arif Hidayat (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
This study investigates the role of tarekat (Sufi orders) as multicultural spaces that integrate diverse values within Islamic mysticism. Through an extensive literature review, the research examines how tarekat, with their inclusivity and adaptability, foster cultural and social harmony. By exploring existing literature on the integration of various cultural practices in Sufism, the study highlights the capacity of tarekat to bridge cultural divides and promote intercultural understanding. The findings underscore tarekat’s role as a model for tolerance and unity, revealing how spirituality and cultural diversity coalesce to foster cohesive community bonds within these orders